2006
DOI: 10.1007/s10461-006-9089-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sex without serostatus disclosure among a national probability sample of HIV patients

Abstract: We examined potential correlates of sex without HIV disclosure within a sample of 875 participants from the HIV Cost and Services Utilization Study. Interviews with each participant assessed sexual activities with up to six recent partners, and this study included both respondent and partnership characteristics. Compared with marriage and/or primary same-sex relationsips, occasional partnerships and one-time encounters were associated with sex with disclosure, and shorter relationships were more likely to invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 38 publications
8
57
2
Order By: Relevance
“…Disclosure to sexual partners is more likely in longer-term, romantic relationships than in casual relationships like one night stands, anonymous partners, group scenes etc. (Duru et al 2006).…”
Section: Disclosure and Social Relationshipsmentioning
confidence: 99%
“…Disclosure to sexual partners is more likely in longer-term, romantic relationships than in casual relationships like one night stands, anonymous partners, group scenes etc. (Duru et al 2006).…”
Section: Disclosure and Social Relationshipsmentioning
confidence: 99%
“…Growing evidence suggests that lack of correct knowledge about HIV and not knowing sex partners' HIV-positive status are significant factors in non-disclosure of HIV serostatus [37][38][39]. A study conducted in China found that unwillingness to disclose HIV seropositive status was associated with misconceptions about HIV transmission [26].…”
Section: Introductionmentioning
confidence: 99%
“…22 In fact, several studies have found differences between these three groups in serostatus disclosure to sex partners. 18,32,34,35 Specifically, HIV-positive MSM are typically less likely to disclose to sexual partners relative to MSW and WSM, citing fears of rejection, issues of confidentiality, and concerns of stigmatization as barriers to HIV disclosure. 19,36 These findings, combined with the disclosure processes model, suggest that disclosure goals and effects on behavior may vary for different sexual behavior groups.…”
Section: Introductionmentioning
confidence: 99%